Millennials, Generation Alpha, and the Sigma Generation Phenomenon: A Qur’anic Perspective on Human Character in the Era of Digital Disruption - Abidurrohman Abidurrohman; Bukhori Abdul Shomad; Masruchin Masruchin; Siti Badi’ah; Budimansyah Budimansyah (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2026)
This study aims to examine the characteristics of the modern Millennial and Alpha generations, as well as the emerging phenomenon of the Sigma generation, from a Qur’anic perspective using a thematic exegesis approach. Although these generational terms are not explicitly mentioned in the Qur’an, their social and psychological characteristics can be analyzed through fundamental Qur’anic concepts such as fitrah, amanah, moral responsibility, balance (tawazun), and social ethics. Using a qualitative research method based on a literature review, this study analyzes Qur’anic verses relevant to the discussion theme through an examination of both classical and modern Islamic literature. The results indicate that the Qur’an provides a comprehensive ethical framework for addressing the challenges faced by generations in the digital age. The Millennial Generation is characterized by adaptability and critical awareness, yet also faces risks of information overload and moral inconsistency, which the Qur’an addresses through the principles of accountability and trust. The Alpha Generation faces challenges in preserving fitrah amidst early exposure to technology, underscoring the urgency of values-based education rooted in Qur’anic teachings. Meanwhile, the Sigma generation reflects a strong level of individual autonomy, which is acceptable within the Qur’anic framework as long as it remains in harmony with piety and social responsibility. This study concludes that the Qur’an remains a relevant and dynamic source of ethical guidance in shaping the character of contemporary generations amid rapid social and technological change.